2008
DOI: 10.1016/j.neulet.2008.05.095
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Ca2+-influx and Ca2+/calmodulin-dependent protein kinase IV activity during in utero hypoxia in cerebral cortical neuronal nuclei of the guinea pig fetus at term

Abstract: Previously we showed that following hypoxia there is an increase in nuclear Ca(2+)-influx and Ca(2+)/calmodulin-dependent protein kinase IV activity (CaMK IV) in the cerebral cortex of term guinea pig fetus. The present study tests the hypothesis that clonidine administration will prevent hypoxia-induced increased neuronal nuclear Ca(2+)-influx and increased CaMK IV activity, by blocking high-affinity Ca(2+)-ATPase. Studies were conducted in 18 pregnant guinea pigs at term, normoxia (Nx, n=6), hypoxia (Hx, n=6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Inhibition of Src kinase prevented the hypoxia-induced increase in tyrosine phosphorylation of calmodulin at Tyr99 and CaM kinase IV showing that it is the Src kinase that mediates the increased Tyr phosphorylation of calmodulin and CaM kinase IV in neuronal nuclei of the cerebral cortex of newborn piglets. [12]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of Src kinase prevented the hypoxia-induced increase in tyrosine phosphorylation of calmodulin at Tyr99 and CaM kinase IV showing that it is the Src kinase that mediates the increased Tyr phosphorylation of calmodulin and CaM kinase IV in neuronal nuclei of the cerebral cortex of newborn piglets. [12]…”
Section: Discussionmentioning
confidence: 99%
“…Ca ++/ calmodulin-dependent kinase IV (CaM Kinase IV), located in the nucleus, phosphorylates the cyclic-AMP response element binding (CREB) protein, a regulator of the transcription of genes of cell survival or cell death pathways. [11,12]…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that EGFR overexpression induces apoptosis through molecular alterations of the glutamate ionotropic receptor N-methyl-D-aspartate (NMDA)-type subunit 2B (GluN2B) ( Tang et al., 2015 ). Modification of the NMDA receptor by oxygen free radicals promotes calcium influx into the cytosol, deactivation of protein tyrosine phosphatases, and activation of EGFR kinase ( Maulik et al., 2008 ; Vibert et al., 2008 ). This series of events causes downstream activation of nuclear CaMKIV, CREB transcription, and the formation of the apoptosome and caspase activation, ultimately leading to DNA fragmentation and cell death ( Mishra et al., 2009 , 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Prolonged cerebral HI leads to a state of primary energy failure, characterized by the depletion of cellular reserves of high energy compounds such as adenosine triphosphate (ATP) and phosphocreatine (PCr), as well as by mitochondrial dysfunction. Electrochemical disruption of the neuronal membrane results in lipid peroxidation, prolonged “open” state of the N-methyl-D-aspartate (NMDA) receptor and a subsequent influx of calcium into the cytosol with the formation of free radicals 1 4 . In addition, calcium influx triggers the formation of focal adhesions through the deactivation of cytosolic phosphatases and activation of protein complexes that extend from the membrane to the nucleus and mitochondria 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%